Comprehensive and Computable Molecular Diagnostic Panel (C2Dx) From Small Volume Specimens for Precision Oncology: Molecular Subtyping of Non-Small Cell Lung Cancer From Fine Needle Aspirates - Su, Jing; Huang, Lynn S.; Barnard, Ryan; Parks, Graham; Cappellari, James; Bellinger, Christina; Dotson, Travis; Craddock, Lou; Prakash, Bharat; Hovda, Jonathan; Clark, Hollins; Petty, William Jeffrey; et al. (Frontiers in Oncology, 2021)
We have been pioneering the Comprehensive, Computable NanoString Diagnostic gene panel (C2Dx) as a promising solution to address the need for a molecular pathological research/diagnostic tool for precision oncology utilizing small volume tumor specimens. In this work, through translating knowledge of subtyping-related gene expression patterns learned in our previous work from public transcriptomic data, we established a highly robust, highly accurate lung cancer subtyping system that demonstrated supreme performance on NanoString platform using microgram-level FNA samples and excellent portability to frozen tissues and RNA-Seq transcriptomic data. This workflow shows great potential in revolutionizing research and clinical practice of cancer molecular diagnosis.